Mapping the Spread of Mercury from Artisanal Mining Activities in Aceh Jaya through Geochemical Surveys - Aflah, Nurul; Mulkal, Mulkal; Aslam, Izzan Nur; Muchlis, Muchlis; Harisman, Hendra (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Illegal gold mining carried out using amalgamation techniques produce mercury waste which can then damage the environment and damage the health of residents. The negative impact due to the use of mercury is dead fish, contaminated river water, water quality below environmental standard quality and spreading in the food chain. This has caused environmental damage, one of which is in terms of land and water. This condition is the basis for conducting deeper research on environmental damage by mercury waste, especially in terms of soil and water. The sampling method used is the Geochemical Method and Geoelectric Method. Geoelectric samples were taken using the superstring R8 tool. Geochemical samples used were soil and water samples which were subsequently tested by the Atomic Absorption Spectrophotometry (AAS) and X-ray Fluorescence (XRF) methods to see the mercury levels that had been scattered in the research location. The study aims to determine the distribution of mercury waste and its levels. This research includes sampling, sample testing, data processing and analysis, and making maps of the distribution of mercury waste through QGis software. From the study, it was found that the distance from the traditional gold mining processing location determines the concentration level (Hg). Analysis using AAS shows that there were 13 samples had mercury concentrations above the critical threshold. From the analysis, it is also known that AAS could not detect mercury levels in soil samples which is different from the results obtained using XRF.